Baseline gut microbiome and metabolites are correlated with changes in alcohol consumption in participants in a randomized Zonisamide clinical trial - Liv R. Dedon; Hanshu Yuan; Jinhua Chi; Haiwei Gu; Albert J. Arias; Jonathan M. Covault; Yanjiao Zhou (Scientific Reports)
Abstract Development and severity of alcohol use disorder (AUD) has been linked to variations in gut microbiota and their associated metabolites in both animal and human studies. However, the involvement of the gut microbiome in alcohol consumption of individuals with AUD undergoing treatment remains unclear. To address this, stool samples (n = 32) were collected at screening (baseline) and trial completion from a double-blind, placebo-controlled trial of zonisamide in individuals with AUD. Alcohol consumption was measured both at baseline and endpoint of 16-week trial period. Fecal microbiome was analyzed via 16 S rRNA sequencing and metabolome via untargeted LC-MS. Both sex (p = 0.003) and psychotropic medication usage (p = 0.025) are associated with baseline microbiome composition. The relative abundance of 11 genera at baseline was correlated with percent drinking reduction (p.adj < 0.1). Overall microbiome community structure at baseline differed between high and low reducers of alcohol drinking (67–100% and 0–33% drinking reduction, respectively; p = 0.034). A positive relationship between baseline fecal GABA levels and percent drinking reduction (R = 0.43, p.adj < 0.07) was identified by microbiome function prediction and confirmed by ELISA and metabolomics. Metabolomics analysis also found 3-hydroxykynurenine, a neurotoxic intermediate metabolite of tryptophan, was negatively correlated with drinking reduction (p.adj = 0.047), and was over-represented in low reducers. These findings highlight importance of baseline microbiome and amino acid metabolites in drinking reduction in AUD participants undergoing zonisamide treatment. It may hold significant value as a predictive tool in clinical settings to better personalize intervention and improve reduction in alcohol consumption in future.